Narasi Akhlak Mulia Dalam Dakwah Digital: Studi Kualitatif Pada Kanal Youtube Ust Irfan Rizki Haas - Novita Sari; Arfit Shafi Anis; Sandra Ayuning Tyas Pratiwi; Azzahra Refa Junia Lestari; Melka Melia Utami; Aulia Dhita Pratiwi; Lilis Permita Sari; Ibnu Rozali (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study aims to analyze the narrative of noble character (akhlaq) in digital da'wah on the YouTube channel of Ust Irfan Rizki Haas, which is motivated by the rapid development of digital media that has transformed the delivery of da'wah from conventional methods into more modern, social media-based approaches. This research employs a qualitative approach using descriptive content analysis, with data collected through digital observation and documentation of selected preaching videos chosen through purposive sampling. The findings indicate that the narrative of noble character in digital da'wah is delivered through a structured storytelling approach that is relevant to daily life, making it capable of attracting audience attention, while the da'wah strategy combines emotional, rational, and sensory approaches, which are proven effective in enhancing audience understanding and engagement. The dominant moral values include husnuzan (positive thinking), gratitude, humility (tawadhu’), consistency (istiqamah), and acceptance (ridha), while audience responses tend to be positive, as they not only understand the message but are also encouraged to change their behavior. Therefore, digital da'wah based on narratives of noble character can serve as an effective communication strategy in shaping character and improving the moral quality of society, especially among the younger generation in the digital era.